Digital thermometer innovation as a body temperature measuring tool for FKIP Mataram university employees during the covid-19 pandemic. Issue 1 (1st January 2022) - Fuadi, H; Susilawati; Doyan, A; Taufik, M; Azhar; Hudha, L S
Abstract: The impact of the Covid-19 pandemic requires that every employee in a university maintains his health. One of the most important body parts to maintain during this pandemic is body temperature. The purpose of this study was to develop a non-contact digital thermometer to measure the body temperature of FKIP employees, Mataram University. The digital thermometer development method starts from literature studies, tool specifications, hardware design, software design and thermometer testing to measure employee body temperature in the morning and afternoon. The results of the digital thermometer test showed that the employee's body temperature in the morning with an average of 33.36 °C and in the afternoon with an average of 33.96 °C. So it can be concluded that the Mataram University FKIP employees who came to work did not experience Covid-19 symptoms.